Characterization of bacteriophage T4-coordinated leading- and lagging-strand synthesis on a minicircle substrate - Salinas, Frank (The National Academy of Sciences, 2000)
The DNA replication complex of bacteriophage T4 has been assembled as a single unit on a minicircle substrate with a replication fork that permits an independent measurement of the amount of DNA synthesis on both the leading and lagging strands. The assembled replisome consists of the T4 polymerase [gene product 43 (gp43)], clamp protein (gp45), clamp loader (gp44/62), helicase (gp41), helicase accessory factor (gp59), primase (gp61), and single-stranded DNA binding protein (gp32). We demonstrate that on the minicircle the synthesis of the leading and lagging strands are coordinated and that the C-terminal domain of the gp32 protein regulates this coordination. We show that the reconstituted replisome encompasses two coupled holoenzyme complexes and present evidence that this coupling might include a gp43 homodimer interaction.